Pengaruh Metode Latihan Drill Terhadap Keterampilan Dasar Free Throw Pada Ekstrakurikuler Bola Basket di SMA Negeri 1 Karawang - Rafky Helri Kurnia; Rahmat Iqbal; Dhika Mahardhika (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study was conducted to determine the effect of the drill method on basic free throw skills in basketball extracurricular at SMA Negeri 1 Karawang. This study is an experimental study to find out whether the drill method has an effect on basic free throw skills in basketball extracurriculars at SMA Negeri 1 Kara-wang. The number of samples is 30 participants in extracurricular activities taken by purposive sampling technique where the sample criteria are based on the class that is willing to be given treatment. The data of this research was carried out with a one group pretest-posttest design. The results obtained through the normal-ity test of the data with the results stating that the pretest data was 0.943 > 0.05 and the posttest 0.945 > 0.05. the results of the pretest-posttest stated that the data were homogeneously distributed and the t-test calculation obtained the value of Sig. (two-tilled) 0.000 <0.05 indicates a significant difference between the results before and after the treatment. it can be concluded from the results of the re-search carried out that it can be stated that there is an effect of the drill training method on the basic freethrow ability in basketball extracurricular at SMA Negeri 1 Karawang.